Aplikasi Smartphone Untuk Anti Bully - Agung A. Pramudji; Benaya Oktavianus Oktavianus; Randy Dwi; Harco Leslie Hendric Spits Warnars (Sekolah Tinggi Teknik - PLN, 2019)
Bullying is aggressive activities not only among school aged children but it can be happened in higher education, office or even in family on daily basis. Bullying involves physical and non physical action which is repeated acted and can be represented in verbal, social and physical thing. Bullying has negative for both perpetrators and victims, the perpetrators will have bad habit which can influence the way their living in the future and particularly for victim it will make them become alone and not open to surrounding relationships.In this paper, we proposed an application which can help to reduce the negative effect of bullying by reporting any bullying happened and do the next action based on meeting result. Moreover, this application will give open private consultation for both perpetrators and victims in order to reduce bullying activities and recognized as bullying. Creating forum for both community who are interested to reduce bullying negatve effect and provide information regarding with negative effect of bullying will help people to educate themselves regarding with bullying. Anti Bully application, IT for Anti Bully, physiatrist Computer Science